Effect of Protein Concentration on the Corrosion Behavior of Magnesium Alloys - MA Yucong, WANG Pengjie, OUYANG Zhengzheng, Mohd TALHA, LIN Yuanhua (Cailiao Baohu, 2025)
When magnesium alloy is used in the human physiological environment， it will be affected by protein.In this work， the corrosion mechanism of a magnesium alloy in phosphate-buffered saline (PBS) containing various concentrations of bovine serum albumin (BSA) (0，0.5， 1.0， 1.5， 2.0， 3.5 and 5.0 g/L) was systematically investigated.Surface characterisation was carried out by Fourier-transform infrared spectroscopy (FTIR)， scanning electron microscopy (SEM)，energy-dispersive spectroscopy (EDS) and contact-angle measurements，whereas electrochemical behaviour was evaluated through potentiodynamic polarisation， electrochemical impedance spectroscopy (EIS) and scanning electrochemical microscopy (SECM).Complementary immersion tests were performed to corroborate the electrochemical findings.To elucidate the time-dependent effect of protein concentration， the electrochemical response and corrosion products of specimens immersed for 1， 3 and 7 d in solutions containing 0， 2.0 and 5.0 g/L BSA were also examined.Results showed that the presence of BSA up to 2.0 g/L reduced the corrosion rate， and the minimum corrosion current density occurred at 2.0 g/L，whereas a higher concentration (5.0 g/L) of BSA significantly accelerated localized corrosion of magnesium alloy surface.In the later stages of immersion， the overall corrosion resistance of the alloy deteriorated.When the BSA concentration was kept below 2.0 g/L， protein molecules formed a monolayer via chemisorption on the alloy surface， leading to a continuous decrease in corrosion rate with increasing BSA concentration.During prolonged immersion， this non-dense adsorbed layer was penetrated by the corrosive medium and consequently lost its protective effect.At 5.0 g/L BSA， protein molecules chelated the metal ions released from the alloy， forming soluble complexes that accelerated corrosion.With further immersion， the continual deposition， detachment and chelation of high-concentration BSA further intensified the dissolution of the magnesium alloy.